Program for prevention of food poisoning in South Timor Tengah Regency with the kitchens of healthy small and medium enterprises - Johannis, Amanda Jelita Eka Riani (BKM Public Health and Community Medicine, 2021)
Objective: This study examines the food poisoning prevention program through the kitchens of healthy small and medium enterprises in South Timor Tengah Regency. Content: Food poisoning has occurred in most parts of South Timor Tengah Regency during the last two years. The Public Health Office of South Timor Tengah Regency has collaborated with food and drug control agencies, as well as across sectors to prevent expired foodstuffs that are still circulating in the market. This has not stopped the cases of food poisoning because food poisoning also occurs due to the lack of knowledge of food vendors and handlers regarding the requirements for good hygiene and sanitation. Food poisoning prevention can be done by approaching people who have direct contact with the community, namely food vendors and handlers. Initial cooperation was carried out with the village head by sending a letter of cooperation agreement related to the implementation of the program that will be implemented. Then through this letter, the village head and village apparatus are tasked with gathering food vendors and handlers selling in the market to participate in counseling activities and cooking demonstrations. The implementation of this activity will be carried out at the village office every month and the preparation of tools and cooking materials will be prepared by the program implementer. If there are not enough cooking utensils, a collaboration can be made by renting cooking utensils belonging to the community. This program is expected to be able to solve the problem of food poisoning in South Central Timor Regency.